Six-month success of radiofrequency ablation in cardiac arrhythmias treatment – experience of our centre - Jurčević Mudrić, Ružica; Angelkov, Lazar; Tomović, Milosav; Kojić, Dejan; Milojević, Predrag (Vojnosanitetski pregled, 2021)
Background/Aim. Numerous trials have shown a high success of radiofrequency ablation (RFA) in the treatment of the patients with cardiac arrhythmias. We aimed to examine the RFA initial success in treatment of different cardiac arrhythmias and the RFA success after 6 months of follow-up. Second aim was to evaluate influence of all clinical and echocardiography parameters on initial and 6-month success and failure of RFA. Methods. The present study included 320 consecutive patients with atrial and ventricular arrhythmias in which RFA was performed during 2014 in the Institute for Cardiovascular Diseases “Dedinje”, Belgrade, Serbia. We evaluated the initial RFA success and success of this procedure after 6-month follow-up. We also investigated the prognostic role of clinical and echocardiography parameters on initial and 6-month success and failure of RFA. Results. The RFA initial success for RFA of atrioventriculas (AV) node and AV nodal reentrant tachycardia (AVNRT) was 100%, RFA of pulmonary veins 99%, RFA of atrial flutter 92%, RFA of premature ventricular complexes (PVC) and the Wolf-Parkinson-White (WPW) syndrome 87%, RFA of ventricular tachycardia 85% and RFA of atrial tachycardia 78%. The success of RFA after 6 months of follow-up for RFA of the AV node was 100%, RFA of AVNRT 94%, RFA of atrial flutter 90%, RFA of WPW syndrome 86%, RFA of pulmonary veins 79% (paroxysmal atrial fibrillation 88% and persistent atrial fibrillation 63% with a significant difference p
Keywords: arrhythmias, cardiac; catheter ablation; electrocardiography; recurrence; serbia.